Assessment of knowledge, attitude, and factors associated with oxygen therapy for critically ill patients among nurses at the University of Gondar Comprehensive Specialized Hospital Northwest, Ethiopia, 2021. (August 2022) - Bizuneh, Yosef Belay; Getahun, Yayeh Adamu; Melesse, Debas Yaregal; Chekol, Wubie Birlie
Abstract: Background: Administering oxygen therapy has an essential role in preventing and managing hypoxemia in both acute and chronic conditions. The aim of this study was to assess knowledge, attitude and factors associated with oxygen therapy for critically ill patients among nurses. Methods: An institutional-based cross-sectional study was conducted from May 23 to June 07 at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, in 2021. A self-administered, structured and validated questionnaire was used. It has socio-demographic characteristics, multiple choice questions, items that measure the possible associated factors and items that were used to assess the level of knowledge and attitude. Epi Data ("The EpiData Association" Odense, Denmark) version 4.6 was used to enter data, and SPSS (IBM) version 20 was used to analyze it. Both bivariate and multivariate logistic regression analyses were used to identify associated factors. Variables with a p value < 0.05 were considered statistically significant. Results: The overall proportion of critically ill patients with good knowledge and a positive attitude toward oxygen therapy was 33% (95% CI: 25.8–37.8) and 53.8% (95% CI: 49–59), respectively. Age (AOR; 1.738, 95% CI: 1.034–2.921), level of education (AOR; 7.731, 95% CI: 2.507–23.846) and guideline (AOR; 4.338, 95% CI: 2.233–8.428) and good level of practice (AOR; 1.885, 95% CI: 1.173–3.030) were discovered to be significant factors associated with good knowledge towards oxygen therapy and the reading guideline was found to be a significant factor associated with a positive attitude toward oxygen therapy (AOR; 1.396, 95% CI: 0.830–2.348). Conclusions: and recommendations: The level of knowledge was low, whereas the attitude of nurses was positive towards oxygen therapy. Reading guidelines, older aged nurses, master holder nurses, and good practice were significant factors associated with good knowledge of oxygen therapy, and reading guidelines was statistically associated with a positive attitude toward oxygen therapy. Thus, nurses need to be aware and skillful regarding the updated oxygen therapy guidelines. They should improve their level of education. Highlights: To assess the level of knowledge and attitude of nurses on oxygen therapy in critically ill patients. An institutional-based cross-sectional survey study was conducted. The overall proportions of good knowledge and a positive attitude toward oxygen therapy were 33% and 53.8%, respectively. The level of knowledge was low, whereas the attitude of nurses was positive towards oxygen therapy.